2020
DOI: 10.4314/ahs.v20i3.40
|View full text |Cite
|
Sign up to set email alerts
|

Research of anti-GAD and anti-IA2 autoantibodies by ELISA test in a series of Moroccan pediatric patients with diabetes type 1

Abstract: Introduction: Type I diabetes (T1D) is an autoimmune disease with a prediabetic, asymptomatic period characterized by the selective destruction of insulin-producing β cells. During the pre-clinical phase, various auto-antibodies are generated against several beta cell antigens such as anti glutamate acid decarboxylase (Anti-GAD), anti tyrosine phosphatase (Anti-IA2). Today, the coupled detection of Anti-IA2 with that of Anti-GAD proves its great importance in the diagnosis and prediction of type 1 diabetes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…T1DM had greater levels of anti-IA2, anti-ICA, and GAD65 antibodies than healthy controls. Zamanfar et al in Iran (9) , Basu et al in India (10) , Belhibaet al in Morocco (11) , and Bravis et al in the United Kingdom (13) all came to a similar result. Beta cell autoimmunity is defined by the presence of diabetes-associated autoantibodies in the bloodstream, which indicates that the cells are being attacked.…”
Section: Detection Of Anti-coxv-b Igg Antibodymentioning
confidence: 68%
See 1 more Smart Citation
“…T1DM had greater levels of anti-IA2, anti-ICA, and GAD65 antibodies than healthy controls. Zamanfar et al in Iran (9) , Basu et al in India (10) , Belhibaet al in Morocco (11) , and Bravis et al in the United Kingdom (13) all came to a similar result. Beta cell autoimmunity is defined by the presence of diabetes-associated autoantibodies in the bloodstream, which indicates that the cells are being attacked.…”
Section: Detection Of Anti-coxv-b Igg Antibodymentioning
confidence: 68%
“….75 U/ml and 58.6 U/ml, respectively compared with 34.6 U/ml, 31.9 U/ml and 43.7 U/ml, respectively, in patients negative for anti-CoxV-B IgG antibodies with highly significant differences (Table 3). (10) , Belhiba et al in Morocco (11) , have reported positive correlations between FBS, HbA1c, and fructosamine values with diabetic patients. According to the data, HbAlc has been found to be a strong predictor of fructosamine.…”
Section: Detection Of Anti-coxv-b Igg Antibodymentioning
confidence: 91%
“…A study conducted in a group of 78 Moroccan children with type 1 diabetes, all under the age of 16, revealed the presence of anti-GAD antibodies in approx. 63% of them, anti-IA2 in 77%, and simultaneously both of the same in 53% of the subjects, notably more commonly in girls [89]. In an Iranian study, the presence of antibodies was confirmed in over 80% of children and adolescents with type 1 diabetes, primarily ICA and Anti-GAD [91].…”
Section: Autoimmune Disordersmentioning
confidence: 92%
“…In the case of auto-aggression, the signal inducing the immune response may originate from an inflammation accompanying the release of antigens due to damage [88]. The immunological markers of type 1 diabetes include antibodies active against pancreatic β cells: Islet-cell antibodies (ICA), insulin autoantibodies (IAA), anti-glutamine acid decarboxylase (anti-GAD), anti-zinc transporter protein 8 (anti-ZnT8), and anti-tyrosine phosphatase antibodies (anti-IA2) [89]. They are detectable many months before clinical symptoms of diabetes, signify the humoral immune response against Langerhans's pancreatic β islet-cells, and are considered to be markers of pancreatic cell destruction.…”
Section: Autoimmune Disordersmentioning
confidence: 99%
“…And from Morocco 39 we a paper on: “anti-GAD and anti-IA2 autoantibodies by ELISA test in a series of Moroccan paediatric patients with type 1 diabetes.” Tackling a social angle of diabetes, a paper from South Africa 40 documents “socio-demographic and modifiable risk factors of diabetes and hypertension among resource constrained patients from rural areas in Mdantsane Township.”…”
Section: Now To Diabetes Mellitusmentioning
confidence: 99%